NAG-1/GDF15 as a tumor suppressor in colorectal cancer: inhibition of β-catenin and NF-κB pathways via interaction with EpCAM - Jaehak Lee; Ilju Kim; Junsun Ryu; Thomas Eling; Seung Joon Baek (Cell Death and Disease)
Abstract NAG-1/GDF15, a tumor suppressor, is synthesized as a pro-form in colorectal cancer (CRC) cells and undergoes cleavage to generate its mature form. While the biological function of pro-NAG-1/GDF15 remains unclear, our study reveals its crucial role in suppressing oncogenic signaling. We demonstrate that pro-NAG-1/GDF15 is predominantly retained within cells, whereas its mature form is secreted into the media. The expression of NAG-1/GDF15, or uncleavable R193A mutant, inhibits β-catenin and NF-κB signaling, key pathways in CRC progression. Mechanistically, the pro-NAG-1/GDF15 interacts with EpCAM, preventing its cleavage and nuclear translocation, thereby reducing β-catenin and NF-κB activity. This inhibition correlates with decreased expression of oncogenic targets such as cyclin D1 and c-myc. In vivo, NAG-1/GDF15 expression significantly reduces tumor growth in cancer xenograft models, accompanied by decreased proliferation and increased apoptosis. Furthermore, analysis of public datasets suggests that high NAG-1/GDF15 expression is associated with improved CRC patient survival. These findings highlight NAG-1/GDF15 via the formation of pro-NAG-1/GDF15 as a promising therapeutic target for cancer, with potential applications in modulating tumorigenic signaling pathways.